Tren Makeup “Mangklingi” dan Krisis Identitas dalam Industri Makeup Artist Indonesia - Melinda Lailatus Zahro; Nevita Sherly Trihapsari; Angelly Rahmadania Putri Kedua; Olivia Zahra Ramadhani . Ys; Berliana Purwanto Shakhib (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
The "mangklingi" makeup trend is gaining popularity in the Indonesian Makeup Artist (MUA) industry, especially since the rise of makeup promotions on social media. The term "mangklingi" refers to a drastic change in facial appearance that significantly differs from one's natural appearance. This trend not only symbolizes a MUA's technical expertise but also establishes new standards for assessing beauty. This study aims to examine how the "mangklingi" makeup trend influences perceptions of beauty and triggers an identity crisis within the Indonesian MUA industry. The method used is a descriptive qualitative approach through literature review, observation of social media content, and interviews with several MUAs and makeup service users. The results indicate that the "mangklingi" trend encourages extreme transformation practices that often ignore clients' natural facial characteristics. This situation has the potential to cause social pressure, reduce self-confidence without makeup, and trigger unhealthy competition among industry players. This study provides a more critical understanding of the dynamics of beauty trends and encourages makeup practices that respect individual identity and uniqueness.